The role of character education and social media literacy in strengthening national resilience among Generation Z in Timor-Leste - Mauzino, Albino; Nursa’ban , Muhammad; Martins, Agus; Herianto, Herianto (Educenter : Jurnal Ilmiah Pendidikan, 2025)
Amidst globalization and digital disruption, a nation's resilience is tested, especially among Generation Z. This study aims to analyze the role of character education and social media literacy in strengthening national resilience among Generation Z in Timor-Leste. A quantitative survey with a cross-sectional design was employed with 256 high school students (Generation Z) in Dili, selected through purposive sampling. Data were collected using the Character Values Scale, Social Media Literacy Scale, and National Resilience Scale. Data analysis included descriptive statistics, Pearson correlation, and multiple linear regression. The findings indicate that both character education (r = 0.23, p < 0.001) and social media literacy (r = 0.13, p < 0.05) have a significant positive relationship with national resilience. However, in a joint regression model that explained 4.7% of the variance in national resilience (F (2,253) = 7.32, p < 0.01), character education emerged as the sole significant predictor (β = 0.23, p = .001). The implication for the field of education is the critical importance of prioritizing a strong character-based curriculum, complemented by digital media literacy, within the national education system to fortify the younger generation against ideological threats.